Investigation of the impact of zeolite shaping and salt deposition on the characteristics and performance of composite thermochemical heat storage systems. Issue 6 (4th January 2023) - Touloumet, Quentin; Postole, Georgeta; Massin, Laurence; Lorentz, Chantal; Auroux, Aline
Abstract : 13X zeolite in powder displays higher storage performances and faster hydration kinetics than 13X in beads. Salt-doped zeolite composite in powder form presents lower pore blockage and higher storage performances than composites in beads. Abstract : Zeolites are promising candidate materials for water-based thermochemical heat storage applications. In this study, 13X and LiX commercial zeolites of different shapes were investigated due to their high thermal stability and storage capacities. Composite materials were prepared by impregnating matrices of 13X zeolite beads (13X(b)), 13X zeolite powder (13X(p)), or LiX beads (LiX(b)) with CaCl2, MgSO4 and LiCl salts (5 wt%). The different zeolites and zeolite@salt composites were characterized using N2 and H2 O sorption isotherms, X-ray diffraction and NMR. The heat and water storage capacities were studied by TG–DSC analysis, as well as the hydration kinetics and the stability over time of the storage capacity. The Dubinin–Astakhov model was applied to the water sorption isotherms in order to better understand the sorption process. It turns out that zeolite shaping has a strong impact on hydration kinetics; moreover, the presence of an inert binder reduces the sorption capacity of 13X(b) compared to 13X(p). The pure zeolites and composites present a very high reversibility of water and heat storage capacities, with a good preservation of storage capacities after 50 simulated cycles of hydration in a water saturated environment. Salt incorporation impacts the porosity (especially for beads) and the environment of the zeolite component, as well as the water sorption behavior, kinetics and process, with a greater influence for LiCl based composites. The impregnation of 13X(b) and LiX(b) zeolites negatively affects the sorption capacities of the composites. This is due to blockage of the zeolite pores, which limits the accessibility of the zeolite structure for water vapor and decreases the contribution of the host matrix to the storage capacity to an extent that is not offset by the relatively small amount of salt added to the system.